Caracterización de hábitos alimentarios y estilos de vida de los niños del Jardín Vaticanitos, Bogotá, D.C. (2008)
ABSTRACT: to characterize food habits and life style of children from the Vaticanitos Garden School, Bogotá, D.C, applying a conceptual frame of the Lund and Burk models to investigate children’s behaviors related to food. Methods: it is a cross-sectional study. 35 children were included in this study, aged 1 to 10 years. They were randomly proportional stratified selected. The data collection was carried out through personal interviews applied to children oldest than 4 years old. Parents, person in charge and teacher were present at the moment of the interview. Results: previous studies showed that 37,5% of the children classified height for age presented low risk of malnutrition, but in the present study risk of malnutrition increased to 42,8%. In this study 77,1% of families have both parents for marital status, mothers and fathers separately reported free union; 54% of the children watch tv almost 2 hours a day and only 42% practice some sport no habitually. The preferred foods reported were yogurt, cookies, fruits and chicken; the less preferred was vegetables and the most frequently consumed was rice, bread, soups and milk. The most common health problems reported were cold and respiratory infections. Conclusions: this study shows the meaning, to promote a positive attitude towards healthy eating behaviors, increasing knowledge and conscious about their food habits in this population. Both parents and teachers recognize the importance of appropriate nutrition in children, emphasizing the benefits of nutritional education to encourage healthy lifestyles.